2021
DOI: 10.4081/mrm.2021.732
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise pattern in patients with persistent dyspnoea after recovery from COVID-19

Abstract: Cause and mechanisms of persistent dyspnoea after recovery from COVID-19 are not well described. The objective is to describe causal factors for persistent dyspnoea in patients after COVID-19. We examined patients reporting dyspnoea after recovery from COVID-19 by cardiopulmonary exercise testing. After exclusion of patients with pre-existing lung diseases, ten patients (mean age 50±13.1 years) were retrospectively analysed between May 14th and September 15th, 2020. On chest computed tomography, five patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 13 publications
7
53
1
4
Order By: Relevance
“…Two studies including COVID-19 patients found V′ O 2 peak 81% and 73% predicted [3,24], which is comparable to our results, whereas another study reported V′ O 2 peak 57% predicted for mechanically ventilated COVID-19 patients [12].…”
Section: Discussionsupporting
confidence: 90%
“…Two studies including COVID-19 patients found V′ O 2 peak 81% and 73% predicted [3,24], which is comparable to our results, whereas another study reported V′ O 2 peak 57% predicted for mechanically ventilated COVID-19 patients [12].…”
Section: Discussionsupporting
confidence: 90%
“…(%) 6(15%) 5(17%) 1(10%) 1 Initial hospitalisation > 48h; no. (%) 14(36%) 8(28%) 6(60%) 0.123 Time before rehabilitation (d); (median[IQR]) 73[34-178] 107[56-240] 32[ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] <.001 Rehabilitation duration (d); (median[IQR]) 66[26-110] 94[63-142] 24[ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ] <.001 PCR+ diagnos...…”
Section: Methodsmentioning
confidence: 99%
“…When grouped together thus on a total of 581 patients, mean values of FEV 1 of 97% predicted, DL CO of 83% predicted, VO 2 max of 82% predicted with an anaerobic threshold of 50% of VO 2 max, V E /VCO 2 slope of 30, preserved breathing reserve and moderately decreased max heart rate altogether offer a CPET profile of deconditioning on the recovery of an acute inflammatory process, prolonged bed rest, and post-traumatic syndrome and depression. Interestingly, there was a tight correlation with a r 2 =0.92, p<0.01 between VO 2 max (in % predicted) and length of hospital stay as calculated on a total of 298 patients from 4 studies [ 13 , 15 , 16 , 20 ]. In one of the studies, CPET was combined with exercise stress echocardiography [ 21 ].…”
mentioning
confidence: 99%
“…These results are in agreement with those of 8 previous mostly smaller studies on a total of 203 patients. (15)(16)(17)(18)(19)(20)(21)(22). When grouped together thus on a total of 581 patients, mean values of FEV 1 of 97 % predicted, DL CO of 83 % predicted, VO 2 max of 82 % predicted with an anaerobic threshold of 50 % of VO 2 max, V E /VCO 2 slope of 30, preserved breathing reserve and moderately decreased max heart rate altogether offer a CPET profile of deconditioning on the recovery of an acute inflammatory process, prolonged bed rest, and post-traumatic syndrome and depression.…”
mentioning
confidence: 99%